COMPARATIVE PUBLIC ADMINISTRATION BETWEEN MALAYSIA AND INDONESIA - Jannial, Jacklyn; Atan, Mohd Izzuddin; Philiphus, Yudik; Johari, Mohd Azri (Universitas Diponegoro, 2024)
An administration is known as a collaborative process that carried by a group of people to achieve goals together; meanwhile a comparative is a process that involve systematic observation of similarities or dissimilarities existed between two or more branches or subjects. A qualitative method of research was used in this article which applies secondary data. Thus, this article aims to study the differences between the public administration between Malaysia and Indonesia in terms of Sociocultural and socioeconomic approach, Political and system approach, and philosophical approach.